Cablaka and Knight Spirit as Banyumas Cultural Identity - Marti; Ita Ridiah (PT Inovasi Pratama Internasional, 2023)
Language is one culture; language is used by groups of people to communicate in life, showing everyday identity. Language also shows that life is social, something in society. The aim of the discussion is identity in Banyumas culture with the languages of cablaka and soul knight. Study This aim is to give a new and descriptive outlook to the identity of the Banyumas people, who are very popular with the Ngapak language, cablaka, or blunt in plain language without a straightforward look. This article is the result of research using local literature. I systematize return with a number of additions. Study This is done with the method of qualitative descriptive. Obtained data with field observations and then next with a search of local literature about Banyuma's identity Search started from A literary work entitled Smile Workman by author Ahmad Tohari narrates the life and culture of the Banyumas people, who have characteristics and the language used to communicate daily. Furthermore, Banyumas people are known for their accepting, patient, and spirited knights. In this study, the researcher found that the language is cablaka, outspoken, awkward, and soulful only in Banyumas, which is scattered in a few covering cities: Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen. There are language similarities, though the accent is a little different. However, Soul Knight is owned by Banyumas, proven by the nickname Banyumas, which is Banyumas City Knight. There are several characteristics typical of the Banyumas people's identity, including the language used: